Implementation approach in legal research - Hamzani, Achmad Irwan; Widyastuti, Tiyas Vika; Khasanah, Nur; Mohd Rusli, Mohd Hazmi (Institute of Advanced Engineering and Science, 2024)
The use of a research approach in legal research will determine the results. There are three categories of approaches in legal research. The normative approach is the most widely used. This research aims to examine how the approach should be implemented in legal research. This research uses a conceptual approach which is still within the scope of the normative approach. Research data was collected by searching articles published in 23 law journals. The results of this research show that the approach to legal research is the use of perspective in discussing legal issues. There are three legal research approaches, namely normative, empirical, and philosophical approaches with all their variants. The normative approach reviews legal problems from a positive law perspective. The empirical approach examines legal problems as a cultural reality. A philosophical approach examines legal problems from an ideal perspective. The approach to legal research should be applied according to the type of research, research data, and level of research. The normative approach is the most widely used. This is because law is mostly understood as a set of rules. Sequentially, of the 256 articles studied, 70% of legal research used a “normative approach”, 19% empirical, and 11% philosophical.